Chemical mutagenesis: selective post-expression interconversion of protein amino acid residues. - Chalker, J; Davis, B (2010)
The ability to alter protein structure by site-directed mutagenesis has revolutionized biochemical research. Controlled mutations at the DNA level, before protein translation, are now routine. These techniques allow specific, high fidelity interconversion largely between 20 natural, proteinogenic amino acids. Nonetheless, there is a need to incorporate other amino acids, both natural and unnatural, that are not accessible using standard site-directed mutagenesis and expression systems. Post-translational chemistry offers access to these side chains. Nearly half a century ago, the idea of a 'chemical mutation' was proposed and the interconversion between amino acid side chains was demonstrated on select proteins. In these isolated examples, a powerful proof-of-concept was demonstrated. Here, we revive the idea of chemical mutagenesis and discuss the prospect of its general application in protein science. In particular, we consider amino acids that are chemical precursors to a functional set of other side chains. Among these, dehydroalanine has much potential. There are multiple methods available for dehydroalanine incorporation into proteins and this residue is an acceptor for a variety of nucleophiles. When used in conjunction with standard genetic techniques, chemical mutagenesis may allow access to natural, modified, and unnatural amino residues on translated, folded proteins.